On Seller Estimates and Buyer Returns - Alex Gershkov; Flavio Toxvaerd (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
This paper revisits recent empirical research on buyer credulity in arts auctions and auctions for assets in general. We show that elementary results in auction theory can fully account for some stylized facts on asset returns that have been held to suggest that sellers of assets can exploit buyers by providing biased estimates of asset values. We argue that, rather than showing that buyers are credulous, the existing evidence can serve as an indirect test of the rationality assumptions underlying auction theory.
urn:nbn:de:bvb:19-epub-13408-6
Keywords: D44; D82; G12; G14; 330; Auctions; information disclosure; seller manipulation; buyer credulity